Case Report: Triplet combination with pirtobrutinib/venetoclax/rituximab in accelerated phase of chronic lymphocytic leukemia - Andrea Serafin; Alessandro Cellini; Francesco Angotzi; Valeria Ruocco; Arianna Bevilacqua; Marco Pizzi; Livio Trentin; Andrea Visentin (Frontiers in Hematology)
The management of accelerated chronic lymphocytic leukemia (A-CLL), an aggressive and rare variant of CLL characterized by increased proliferation and histologically defined features, remains a challenging area with limited evidence. A-CLL is distinguished by its intermediate behavior between indolent CLL and Richter Transformation (RT), often associated with high-risk genetic markers and rapid disease progression. Existing data from the era of targeted therapies are scarce, complicating the standardization of treatment approaches and prognostic assessments. While novel agents such as Bruton Tyrosine Kinase inhibitors (BTKi) and venetoclax have shown promise in individual cases, comprehensive evaluations in A-CLL are lacking. We present two cases of CLL that progressed through various phases, including the accelerated phase and suspected RT. These cases highlight the distinct clinical features of A-CLL, including elevated LDH levels, high SUV on PET-CT, and adverse genetic markers, alongside the limitations of traditional chemoimmunotherapy. Importantly, we detail the novel use of a triplet therapy combining a non-covalent BTKi, venetoclax, and rituximab, demonstrating promising outcomes that provide valuable insights into managing this aggressive CLL variant in the era of targeted therapies.